Współpraca i konkurencja w opiniach przedsiębiorców z obszarów wiejskich województwa lubuskiego - Wojewoda, Izabela (Co-Operation and Market Competition in the Opinion of the Country Area Entrepreneurs of Lubuskie Voivodeship, 2006)
The article presents the chosen outcomes of the research on entrepreneurs of service companies registered in the country areas of Lubuskie voivodeship. They concern the co-operation and ways of competition within the local service market. The co-operation between the entrepreneurs of small service companies is the result of existence of non-formal tights, friendship, acquaintances, specific business climate created by the country community. The entrepreneurs avoid the competition, for the benefit of common co-operation or limit their competitive activities through certain division of the local market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 501-507